Presenças incômodas no Porto de Santos: uma etnografia das relações entre humanos, pombos, grãos e outros sujeitos - Moreno, Sarah Faria (2019)
Pigeons are birds that coexist intensely with humans all over the globe, serving as their messengers, as a sign of peace, or a religious icon. In the last decades, however, pigeons seem to have been simply reduced to an urban plague. Before such ambivalence of the pigeons, I set out to ethnography the relations between people and pigeons at the Port of Santos, on the south coast of São Paulo state, where the pigeons are too many and present in an annoying way, due to the large load handling of grains there. From my ethnographic research I show how the pigeons are simultaneously signs and agents; also that biological classifications are not enough to understand the relations between people and pigeons, and how these relations have much to say not only about imposed classifications to pigeons, but also about disputes over urban and portuary spaces, also, institutional and political conflicts. In this way, as of anthropological approach, I think that this research constitutes one more step to our thinking of some sort of different way of living with, on what humans and no humans can live together.